Dilithium and Magnesium Alkanediides and 1‐Oxaalkanediides. Issue 21 (31st August 2017) - Fischer, Reinald; Görls, Helmar; Krieck, Sven; Westerhausen, Matthias
Abstract : Dilithium and magnesium alkanediides of the types Li(CH2 )n Li and [Mg(CH2 ) n ] x represent substance classes with a long tradition, however, the interest in these compounds ceased in recent years. Numerous reasons account for the vanishing attention such as challenging synthetic procedures, poor to moderate yields, complex structures in solution and the solid state, and complex equilibria in solution. Degradation processes (ether degradation, β‐hydride elimination, indirect reduction reactions) increase the intricacy of these compounds because these degradation products take part in the solution equilibria. Thus, chloride and hydride ions are able to act as templates for lithium cages yielding e.g. [(Et2 O)4 Li] + [Li12 (C4 H8 )6 (@‐ X )] – ( X = H, Cl) with an X ‐centered Li12 icosahedron. Despite these challenges, the dilithium and magnesium alkanediides are a fascinating substance class with a rich chemistry by its own (such as Schlenk‐type equilibria) and as metalating and reducing reagents. The enormous sensitivity toward moisture (hydrolysis reactions) and air (oxidation processes) and reactivity toward ethereal media (ether degradation reactions) also interferes with the dianionic alkanes because alkoxide and oxide ions are strong Lewis bases and as such, are easily integrated in the structures as bridging anions or centers of metal cages. Thus, aerial oxidation leads to insertion of an oxygen atom into the metal–carbon bond yielding 1‐oxaalkanediides. Alternatively, magnesium 1‐oxaalkanediides can be prepared by a two‐step protocol from chloroalkanol, starting with deprotonation of the alcohol functionality with a Grignard reagent and a subsequent reduction of the C–Cl unit with magnesium turnings. This protocol leads to compounds of the type [{MgO(CH2 ) n } x (MgCl2 ) y ] with additional ether bases saturating the coordination spheres of the magnesium atoms. All these reactions (increasing degradation processes and reactions with inadvertently introduced traces of oxygen and moisture) limit the durability of such solutions, subsumed as aging of these dilithium and magnesium dialkanediide stock solutions, which lead to a changing (decreasing) reactivity of such reagents. Abstract :